Zakat: Solusi Pengentasan Kemiskinan - Nur Qomari (Iqtishodia: Jurnal Ekonomi Syariah, 2017)
Poverty is one of the problems that become a homework for developing countries including in Indonesia. Some goverment programs that have been launched in order to overcome poverty do not seem reliable enough to be a solution to the problem, instead of succeeding, the poverty rate in Indonesia is getting higher. In Islamic economics, zakat is a concentrated discourse as one of the alternatives to breaking the problem of poverty. The majority of Indonesia’s Muslim population, provides a great opportunity for the achievment of poverty alleviation missions, it is believed that as more and more Muslim aware of the obligation to pay zakat, the greater the potential of collected zakat. Zakat wise management and fair distribution and equitable, of course, be one requirment taht must be fulfilled so that function of zakat can be felt by all society layer. This paper use the literature approah and draw the concusion that the potential of zakat in Indonesia reached a fantastic figure. Zakat can be used as an alternative solution to the problem of poverty in Indonesia. With professional management, the people of Indonesia must be optimistic that the poverty rate will soon decline. Keyword: Poverty, Zakat, Islamic Economics.